Pengaruh Pembiayaan Bank Syariah Terhadap Produk Domestik Regional Bruto Di Sulawesi Selatan (Sebelum dan Selama Pandemi Covid-19) - Emily Nur Saidy (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2023)
The covid-19 pandemic has exacted on the global economy, including in Indonesia. The GDP growth rate was reported to be minus 2,07 percent in 2020. South Sulawesi is one of the provinces affected by the covid-19 pandemic. This research tried to examine the influence of Sharia bank financing on Gross Regional Domestic Product before and during the covid-19 pandemic in South Sulawesi. This paper seeks to empirically explore the impact that Sharia bank financing had on the Gross Regional Domestic Product of five cities/districts in the South Sulawesi region (Makassar, Parepare, Bone, Palopo, and Maros) before and during the covid-19 pandemic. The analysis method in this research has used the Weighted Least Square (WLS) regression testing simple. Data were analyzed using panel data for 2017-2021 derived from the Financial Services Authority (OJK) sites and the Central Statistics Agency of South Sulawesi (BPS) sites. This paper proves that Sharia Bank financing has had a positive and significant influence on the Gross Regional Domestic Product of South Sulawesi before and during the covid-19 pandemic, especially in five Regencies/Cities such as Makassar, Maros. Parepare, Bone, and Palopo.